Archetypes and Basic Strategies of Technology Decisions: Understanding the likely impact of a new technology and the uncertainty associated with it can help managers determine the most efficient, effective approach to decision making. Issue 2 (3rd March 2016) - Lingens, Bernhard; Winterhalter, Stephan; Krieg, Lukas; Gassmann, Oliver
OVERVIEW: Technology decisions are of central importance to firms focused on innovation. Research has provided support for a wide variety of approaches to technology decision making. This proliferation of approaches, however, means managers face the challenge of choosing the right approach for a given decision. Through case studies and workshops with a wide range of firms, we have developed a tool to assist managers in selecting appropriate approaches for the specific technology decision at hand.